Determinants of collateral☆ - JIMENEZ, G; SALAS, V; SAURINA, J (Journal of Financial Economics, 2006)
We estimate a comprehensive model of the determinants of collateral in loans extended to business firms. We use a panel data on a sample of bank loans to Spanish firms from 1984 to 2002. Consistent with theories that view collateral as a solution to adverse selection problems, our results provide direct evidence of a negative association between collateral and a borrower's risk. We also present evidence on previously unexplored determinants of collateral such as credit market competition, lender type, and the business cycle.